2022
DOI: 10.1007/s00415-022-11296-4
|View full text |Cite
|
Sign up to set email alerts
|

Humoral response and safety of the third booster dose of BNT162b2 mRNA COVID-19 vaccine in patients with multiple sclerosis treated with ocrelizumab or fingolimod

Abstract: Background The assessment of the safety and the humoral response to a third booster dose of the BNT162b2 mRNA COVID-19 vaccine is relevant in patients with Multiple Sclerosis (pwMS) treated with Ocrelizumab (OCR) or Fingolimod (FNG). Methods Serum samples were collected from Healthy controls (HCs) and pwMS treated with OCR or FNG at the following time-points: before the first of two vaccine doses (T0); 8 (T1), 16 (T2), 24 (T3) weeks after the first dose; w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 25 publications
8
16
0
Order By: Relevance
“…Regarding the effects of the first booster dose of vaccine, at T3 we observed a strong upregulation of the humoral response in both treated and untreated patients, although the humoral responses observed in patients treated with anti-CD20 (OCR) and FTY remained significantly lower than those observed in untreated patients ( Table 3 and 4 ). Yet, the first booster dose significantly increased anti-S levels even in most patients taking these immunosuppressive therapies, in line with other studies ( 14 ). For example, in anti-N negative patients under OCR and FTY, median anti-S antibody levels were, respectively, 40.5 and 28.6-fold higher at T3 than at T1.…”
Section: Discussionsupporting
confidence: 89%
“…Regarding the effects of the first booster dose of vaccine, at T3 we observed a strong upregulation of the humoral response in both treated and untreated patients, although the humoral responses observed in patients treated with anti-CD20 (OCR) and FTY remained significantly lower than those observed in untreated patients ( Table 3 and 4 ). Yet, the first booster dose significantly increased anti-S levels even in most patients taking these immunosuppressive therapies, in line with other studies ( 14 ). For example, in anti-N negative patients under OCR and FTY, median anti-S antibody levels were, respectively, 40.5 and 28.6-fold higher at T3 than at T1.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, ways to improve/optimize vaccination responses will be beneficial ( Sullivan et al, 2022 *). Although, repeated boosting can increase the titres of SARS-CoV-2 specific-antibodies in some people ( Tallantyre et al, 2022a , Milo et al, 2022 , Capuano et al, 2022 , Achtnichts et al, 2022 ), uninterrupted S1PR modulator treatment is currently often associated with a blunted vaccination response ( Pitzalis et al, 2021 , Tallantyre et al, 2022a , Louapre et al, 2022 *), ( Meyer-Arndt et al, 2022 , Akgün et al, 2022 *), ( Scn et al, 2022 ). A long-period of fingolimod discontinuation, to allow recovery of lymphocytes, may increase the chance of a vaccine-induced antibody response, but risks disease breakthrough that can occur within a few weeks of discontinuation ( Barry et al, 2019 , Achtnichts et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…We also showed a strong relationship between antibody development and age and duration of treatment, as well as between antibody titer and age and duration of treatment. Therefore, we cannot afford not to recommend vaccination in MS patients treated with fingolimod, especially as research has shown that the third booster dose (mRNA vaccine in the study) revives the humoral response independently of any clinical variables [49] . Further studies on this topic are needed to support our results, especially regarding the influence of the duration of treatment on antibody development and titer (scarce data at present), although one study supports our point and also shows a relationship between treatment duration and vaccine response [50] , ideally with a larger sample size and a measurement of cellular immunity.…”
Section: Discussionmentioning
confidence: 99%